Rancang Bangun Sistem Inventory Pada Izara Batik Menggunakan Metode Prototype - Hayati, Nur; Fanani, M.Rudi; Hakim, Mujibul (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
Inventory as a system in a company related to the stock of goods is required to provide all information about the availability of raw materials, semi-finished goods or finished goods. Inventory of goods is an activity that will always change and as the main element that will continue to rotate. If the Inventory is too large, it can cause high cost burdens so that it needs to be minimized while still meeting consumer demand. Therefore, to overcome this problem, a system is needed to be able to manage and monitor the availability of goods in order to meet consumer demand effectively and efficiently. The design of the Inventory system at Izara Batik using the Prototype method aims to manage and monitor the availability of existing goods with actual consumer needs more effectively and efficiently. The Prototype method has the first stage, namely communication, quick plan, modeling quick design, construction of Prototype, deployment delivery and feedback. The system that has been built is then tested using alpha testing, namely blackbox testing. The test results show that all functions operate properly and according to their functions. Therefore, this Inventory system is able to overcome problems at Izara Batik, making the transaction process in the warehouse easier and more efficient and the data on goods owned can be managed better.